Change of the rural area in the knowledge society - Kujath, Hans Joachim; Dehne, Peter; Stein, Axel (Raumforschung und Raumordnung | Spatial Research and Planning, 2019)
In the knowledge society, spatial structure is differentiated, and as a result of this process the rural area no longer appears as a homogenous entity. The “reflexive modernity” of the knowledge society does not seem to know any determinism concerning spatial development-differences, but rather provides new scope to people for acquiring and valorizing different areas. New development impulses could be triggered in the so far peripherally assessed rural area through those extended options. In order to review these assumptions, this paper asks from a theoretical perspective how the cultural, social, economic and technical dimensions of the knowledge society interact with space, and what challenges and strategies may arise for rural areas. The empirical verification is based on results of a working group of the Academy of Spatial Research and Planning (ARL) about the knowledge society in rural-peripheral regions and more qualitative and quantitative studies about the topic. Analysis shows that in many, but not in all regions new knowledge society shaped life cultures evolved differentiating from urban social models. They prove a new attractiveness of the rural area, which are also expressed in knowledge-based projects of culture, education, public services and entrepreneurial commitment. There are a lot of examples especially in economic competitive regions but also in peripheral regions suffering population loss. It needs more studies to determine how the approaches can be used by public and private players to promote the knowledge-society based change. They could help using the gained experience in successful regions for political and planning support in peripheral rural towns and regions.